2022
DOI: 10.3390/nu14153159
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Omija (Schisandra chinensis) Extract Mixture on the Improvement of Hyperglycemia: A Randomized, Double-Blind, and Placebo-Controlled Clinical Trial

Abstract: A previous animal study demonstrated that the administration of Omija extract and soybean mixture (OSM) improved glycemic control in the type 2 diabetes model. In this study, we conducted a 12-week, randomized, double-blinded, and placebo-controlled clinical trial to determine the effects of OSM in humans with hyperglycemia. Participants with fasting plasma concentrations of 100–140 mg/dL were enrolled (n = 80) and administered either OSM or placebo products for 12 weeks. The outcomes included measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the case of E. senticosus , arterial hypertension was recognized as a contradiction for use [ 106 ]. In turn, S. chinensis in a study by Kim [ 107 ] did not induce any serious negative effects. Only painful complaints were recorded; however, no clear association with the extract was observed.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of E. senticosus , arterial hypertension was recognized as a contradiction for use [ 106 ]. In turn, S. chinensis in a study by Kim [ 107 ] did not induce any serious negative effects. Only painful complaints were recorded; however, no clear association with the extract was observed.…”
Section: Discussionmentioning
confidence: 97%
“…We suggest that the preparation of therapeutic agents using not only the Schisandra extract but also natural extracts containing various active compounds may be potentially used to treat OA. Furthermore, some studies have demonstrated the use of S. chinensis extract in clinical trials and applications for various diseases 60,61 . Therefore, further research is needed to confirm its efficacy in treating patients with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have demonstrated the use of S. chinensis extract in clinical trials and applications for various diseases. 60 , 61 Therefore, further research is needed to confirm its efficacy in treating patients with OA. Hence, we anticipate that through the outcomes of this study and subsequent research endeavours, S. chinensis extract may effectively mitigate the underlying pathogenesis of human OA.…”
Section: Discussionmentioning
confidence: 99%